Main lobe interference suppression method of Skywave OTHR based on fast-time STAP. Issue 1 (1st December 2022) - He, Tao; Sun, Guangjun; Ding, Shujuan
Abstract: For the sky-wave over-the-horizon radar (OTHR), how to effectively suppress the radio frequency interference (RFI)from the main-lobe direction is a problem. To solve this problem, this paper proposes a new space-fast time adaptive processing (fast-time STAP) which merges the matched filter coefficients used for pulse compression and the time steering vector of fast-time STAP. To compare with conventional methods, the method improves the match between the space-time steering vector of fast-time STAP and the real target signal, while the RFI and the noise from RFI are effectively suppressed by the interference-plus-noise covariance matrix which is composed of raw data. At the same time, the signal-to-noise ratio is improved. Compared with the traditional method, this method can be better applied to practical engineering. The results of computer simulation and experiments with real radar data verify the effectiveness of the proposed method.